Evaluating the network adequacy of vision care services for children in Arizona: A cross sectional study - Rizwana Biviji; Nikita Vora; Nalani Thomas; Daniel Sheridan; Cindy M. Reynolds; Faith Kyaruzi; Swapna Reddy (AIMS Press, 2024)
Background: Vision challenges are among the most prevalent disabling conditions in childhood, affecting up to 28% of school-age children. These issues can impact the development, learning, and literacy skills of affected children. While vision problems are correctable with timely diagnosis and treatment, insufficient networks can impede children's access to comprehensive, and high-quality care. Objective: The study aims to determine where pediatric vision care network adequacy exists in the state of Arizona and where there are gaps in receiving vision care for children. Methods: This cross-sectional study assessed the adequacy of pediatric vision care networks in Arizona through a "secret shopper" phone survey. Calls were made to practices that accept Arizona's Medicaid program, Arizona Health Care Cost Containment System (AHCCCS) and/or commercial insurance. Providers were contacted following a standardized script to schedule routine appointments on behalf of 10 and 3-year-old patients enrolled in either Medicaid or commercial health insurance plans. The study examined various components of children's access to vision care services, including the reliability of provider directory information, time until the next available appointment, bilingual service offerings, ages served, region of practice and types of care available. Results: A total of 556 practices in Arizona were evaluated through simulations as patients on AHCCCS, and 510 practices were assessed through simulations as patients with commercial health insurance plans. The average wait time for the next available appointment was 13 days for both insurance types. Alarmingly, up to 74% of vision care practices in Arizona do not serve children covered by AHCCCS. Furthermore, only 41% provide services to children 5 years and younger. Conclusions: Our findings underscore the need to improve access to vision care services for children in Arizona, especially racial/ethnic minorities, low-income groups, and rural residents.